2014
DOI: 10.1093/jnci/dju268
|View full text |Cite|
|
Sign up to set email alerts
|

Activated Lymphocyte Recruitment Into the Tumor Microenvironment Following Preoperative Sipuleucel-T for Localized Prostate Cancer

Abstract: BackgroundSipuleucel-T is a US Food and Drug Administration–approved immunotherapy for asymptomatic or minimally symptomatic metastatic castration-resistant prostate cancer (mCRPC). Its mechanism of action is not fully understood. This prospective trial evaluated the direct immune effects of systemically administered sipuleucel-T on prostatic cancer tissue in the preoperative setting.MethodsPatients with untreated localized prostate cancer were treated on an open-label Phase II study of sipuleucel-T prior to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(151 citation statements)
references
References 20 publications
(21 reference statements)
6
136
3
1
Order By: Relevance
“…4 We now show that neoadjuvant sipuleucel-T elicits Th1 response that includes CXCL10 and a CD8 expression signature. To our knowledge, this is the first report to confirm that intratumoral Th1 immune response are specifically induced by sipuleucel-T treatment and are consistent with the Th1 immune responses that have been detected in the circulating T cells.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…4 We now show that neoadjuvant sipuleucel-T elicits Th1 response that includes CXCL10 and a CD8 expression signature. To our knowledge, this is the first report to confirm that intratumoral Th1 immune response are specifically induced by sipuleucel-T treatment and are consistent with the Th1 immune responses that have been detected in the circulating T cells.…”
Section: Discussionmentioning
confidence: 65%
“…For all five paired cases examined, an upregulation of Th1/Th2 ratio was observed with treatment (p < 0.01, Figure 1E). We had previously shown that sipuleucel-T treatment was associated with an increase in infiltration of CD3+, CD4+Foxp3- and CD8+T cells into the tumor microenvironment 4 To confirm reliability of the calculated lymphocyte scores, we assessed their correlation with CD3, CD8, Foxp3 and CD20 staining by immunohistochemistry (IHC), scored by the frequency of positive staining at the tumor interface. The total T cells, CD8 T cells and Treg scores were significantly correlated with IHC scores for CD3, CD8 and Foxp3, respectively (p = 0.02).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations